The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/1750-3841.15804
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of antioxidant peptides from hairtail surimi hydrolysates and their effects on beef color stability

Abstract: The antioxidant peptides extracted from plants or animals have shown great potential in preventing food quality deterioration caused by oxidization. Here, peptide fractions obtained from hairtail surimi hydrolysates (HSH) were investigated for structure and color‐protective effect. The results showed the <3 kDa fraction obtained from HSH by ultrafiltration could be separated into five major fractions (A–E) by gel chromatography, among which fraction A possessed the highest antioxidant activities. This fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 47 publications
(62 reference statements)
0
0
0
Order By: Relevance
“…The sturgeon peptide, GDRGESGPA (845.37 Da), having glycine and alanine, showed DPPH • scavenging activity of 40% [101]. Hairtail surimi peptide, DLYANTVLSGGTTMYPGIADR (2.2 kDa), having leucine, glycine, isoleucine, and alanine, showed DPPH • and • OH scavenging activity of 67.07% and 62.08%, respectively [100]. Furthermore, oyster peptide, LANAK (515.29 Da), showing DPPH • scavenging activity of 83.79%, also contained leucine and alanine [87].…”
Section: Antioxidant Effects Of Bioactive Peptides From Marine Animal...mentioning
confidence: 99%
“…The sturgeon peptide, GDRGESGPA (845.37 Da), having glycine and alanine, showed DPPH • scavenging activity of 40% [101]. Hairtail surimi peptide, DLYANTVLSGGTTMYPGIADR (2.2 kDa), having leucine, glycine, isoleucine, and alanine, showed DPPH • and • OH scavenging activity of 67.07% and 62.08%, respectively [100]. Furthermore, oyster peptide, LANAK (515.29 Da), showing DPPH • scavenging activity of 83.79%, also contained leucine and alanine [87].…”
Section: Antioxidant Effects Of Bioactive Peptides From Marine Animal...mentioning
confidence: 99%
“…During freezing storage, the protein of surimi will undergo freezing denaturation, and the activity of endogenous protease will decrease (Zhang et al., 2020a), resulting in loss of emulsification, gel, and other important functional properties (Nikoo et al., 2016). In addition to the denaturation of surimi and its proteins caused by low‐temperature storage, oxidation is another reason for protein denaturation of surimi, and protein oxidation still exists in the process of freezing storage (Wang et al., 2021). Some studies have reported the mechanism of protein oxidation in surimi products, which can be summarized as a free radical chain reaction directly triggered by reactive oxygen species and active nitrogen or indirectly triggered by secondary products produced by oxidation (Soladoye et al., 2015).…”
Section: Introductionmentioning
confidence: 99%